The Effect of TANDUR Type Quantum Teaching on Students’ Motivation and Psychomotor Skills in Learning the Area of Plane Figures in Elementary Schoo - NISA’, CHOIRUN; HARRIS, TAUFIQ; FAIZIN, AHMAD (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to investigate the effect of the Quantum Teaching model TANDUR (Tumbuhkan–Alami–Namai–Demonstrasikan–Ulangi–Rayakan) on students’ motivation and psychomotor skills in learning the area of plane figures (triangles, squares, and rectangles) among fifth-grade elementary school students. A quasi-experimental design with pretest-posttest control group was employed involving 50 students from two public elementary schools in Pasuruan Regency, East Java. The experimental group (n = 24) received instruction using the TANDUR model, while the control group (n = 26) followed conventional teaching methods. Data were collected through motivation questionnaires based on Keller’s ARCS model and psychomotor observation rubrics, then analyzed using descriptive statistics, normalized gain (N-gain), and independent samples t-test. Results showed a statistically significant improvement in both motivation (p < 0.05; N-gain = 0.68, moderate) and psychomotor skills (p < 0.01; N-gain = 0.73, high) in the experimental group compared to the control group. These findings suggest that the TANDUR-based Quantum Teaching model effectively enhances affective and psychomotor domains by engaging students in experiential, contextual, and celebratory learning activities aligned with Piaget’s concrete operational stage. This study contributes to the development of student-centered mathematics pedagogy in primary education.